ANALISIS PENDAPATAN NELAYAN PURSE SEINE: STUDI KASUS PADA KM. HAJRA DI KELURAHAN LAPULU KECAMATAN ABELI KOTA KENDARI - Dedi, Urbanus; Siang, Roslindah Daeng; Annaastasia, Nurhuda; Risfandi, Risfandi; Abdullah, Abdullah (Fakultas Ekonomi Dan Bisnis Universitas Sulawesi Tenggara, 2025)
This study aims to determine the income level of fishing business using purse seine in Lapulu Village, Abeli District, Kendari City. Research data were obtained through observation, interviews and recording and documentation on the KM purse seine boat. Hajra. Data were analysed by revenue analysis and R/C ratio. The results showed the amount of fishing production of purse seine fishermen averaged per trip in the peak season as much as 8,348 Kg, medium season as much as 3,678 Kg, and lean season as much as 1,579 Kg. The average revenue value of purse seine fishermen per trip in the peak season was Rp138,102,000, in the medium season was Rp65,464,000, and in the lean season was Rp30,864,667. The R/C ratio value of 1.45, meaning that if every Rp1,000 cost sacrificed per trip by purse seine fishermen will get an income of Rp1450/trip. The R/C ratio value is greater than 1, it can be concluded that the fishing business using purse seine fishing gear is profitable and feasible to develop.